Ethiopia : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1999)
This paper reviews economic developments in Ethiopia during 1995-99. It provides an update on macroeconomic performance and structural reforms during FY96-FY99 (fiscal year ended July 7), when Ethiopia-as Africa's second most populous country and one of the world's poorest nations-continued to make strides in transitioning to a market-based economy and alleviating widespread poverty. The paper also highlights the major challenges in the areas of financial sector liberalization, civil service reform, and privatization.